Piezoelectric actuators for bone mechanical stimulation: exploring the concept. - Reis, J (2013)
Arthroplasty is liable to cause intense changes on strain levels and distribution in the boné surrounding the implant, namely stress shielding. Several solutions have been proposed for this, namely design variations and development of controlled-stiffness implants. A new approach to this problem, with potential application to other orthopaedic problems and other medical fields, would be the development of smart implants integrating systems for bone mechanical stimulation. Ideally, the implant should presente sensing capability and the ability to maintain physiological levels of strain at the implant interface. Piezoelectric materials’ huge potential as a mean to produce direct mechanical stimulation lies on the possibility of producing stimuli at a high range of frequencies and in multiple combinations. The present in vitro and preliminary in vivo studies were a first step towards the validation of the concept.